2007
DOI: 10.1111/j.1538-7836.2007.02597.x
|View full text |Cite
|
Sign up to set email alerts
|

A proposed structural model of human protein Z

Abstract: Analysis of structures and sequence similarities of the vitamin K-dependent (VKD) proteins in the blood coagulation pathway has shown that these proteins have evolved through a series of gene duplications and diversification, acquiring a degree of functional diversity in the process [1][2][3]. Protein Z (PZ) is a VKD plasma glycoprotein that is highly conserved across different species. It is homologous to the blood coagulation factors VII (FVII), FIX, FX, and protein C (PC). However, PZ differs from other coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…2A), which brings the orientation of the SP domain close to the EGF1 domain. This bend was also observed in our previous extended The multiple sequence alignment for Gla, EGF1, and EGF2 domains is the same as our previous PZ paper ( Lee et al 2007) (part of EGF2 is shown in the alignment). The modified regions are color coded as shown in the legend.…”
Section: Structural Features Of Pzasupporting
confidence: 85%
See 3 more Smart Citations
“…2A), which brings the orientation of the SP domain close to the EGF1 domain. This bend was also observed in our previous extended The multiple sequence alignment for Gla, EGF1, and EGF2 domains is the same as our previous PZ paper ( Lee et al 2007) (part of EGF2 is shown in the alignment). The modified regions are color coded as shown in the legend.…”
Section: Structural Features Of Pzasupporting
confidence: 85%
“…For substrate recognition and catalytic activity, the serine protease domain must have the following key characteristics (chymotrypsinogen numbering is used): the His57-Asp102-Ser195 catalytic triad, a selectivity S1 site composed of Asp189, Gly216, and Gly226, an oxyanion hole formed by the backbone NHs of Gly193 and Ser195, a proximal hydrophobic S2 pocket, a distal hydrophobic S3 pocket, and the salt bridge between Asp194 and N-terminal residue (Ile16) (Perona and Craik 1995;Czapinska and Otlewski 1999;Hedstrom 2002). In order to identify a reasonable primary sequence for the activated form of PZ, the multiple sequence alignment of PZ with FVII, FIX, FX, and PC was used as the starting point (Lee et al 2007). The amino acid residues in PZ corresponding to the key residues (above) that confer these serine protease characteristics were first modified based on the multiple sequence alignment.…”
Section: Design Of the Pza Sequencementioning
confidence: 99%
See 2 more Smart Citations
“…Disulfides are present at the predicted positions of 131-132, 133-241, 163-179, and 287-301. Also as expected, the residues that substitute for the catalytic His and Ser of functional trypsin family proteinases (here Lys-178 and Asp-313, respectively) in the pseudo-active site are close together, and near the top of the molecule (27) (Fig. 1A), with C␣-C␣ separation of 8.3 Å, the same as in fXa, although the third residue of the triad is the normal Asp (Asp-221).…”
Section: Structure Of the Zpi⅐pz ⌬Gdmentioning
confidence: 76%